Profilaktichesko-reabilitatsionnye tekhnologii v sisteme podgotovki sportsmenov: osnovnye polozheniya, perspektivy razvitiya i ispol'zovaniya - Orlovskaya, Yu. V. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The purposes of the presented study were the theoretical substantiation and practical approbation of prophylactics- rehabilitation technologies in conditions of sport training process. The modern system of prophylactics and rehabilitation can be presented as five functional blocks: I. Entrance to system; II. The medical-pedagogical analysis; III. Realization of prophylactics-rehabilitation measures in the system of athlete's training; IV. High-grade individual participation in sport activity (educational-training and competitive); V. System's external components. The positive results had been received in all experiments. The losses of educational-training loadings were reduced, the traumatism was decreased, the general and special efficiency was stabilized.